THE USE OF GOOGLE CLASSROOM TO TEACH ENGLISH FOR COLLEGE STUDENTS - Dadan Hidayat (INOVISH JOURNAL, 2021)
The education system implemented in Indonesia in the new normal era underwent changes. Prevention of transmission of the corona virus by social distancing to avoid potential crowds is the main reason children have to go to school from home. Changes that occur include education which was originally face-to-face to online or online only. Another thing that has changed is the adjusted learning targets and also the adaptation of the curriculum used. education is required to adapt immediately. Education must not stop just because of the impact of the spread of Covid-19. One of the online learning media that is currently developing and starting to be used is Google Classroom. Google Classroom is a special application that is used for online learning carried out remotely and can be used anywhere. In using the Google Classroom application, it contains services for users such as being able to send assignments in the form of documents, photos, and learning videos to students related to the material discussed. This research aimed to know the benefits of google classroom and how the teachers and students use google classroom The methods used in this survey were library surveys and interviews. Arikunt discovers that literary studies in research are a way to collect data by finding information from books, newspapers, magazines, and other literature to build a theoretical foundation. I did (Arikunto, 2006)In addition to this opinion, literary research is a data collection technique by researching books, literature, records, and reports related to solved problems (Nazir, 1988)Data and information are available from academic books, research reports, academic papers, sets of rules, encyclopedias, diplomas, and other written and digital sources. In addition, we conducted a similar survey and collected data on Google classrooms and education usage during the pandemic. researcher concluded that the use of google classroom in coaching English for the pandemic is compelling withinside the mastering manner because the academics and college students can without problems to get entry to the google classroom. The instructor can set up the elegance, supply the material and supply the assignmentKeyword : During learning, Pandemic Covid-19, Google Classroom